The Relationship between Teaching Competencies and the Achievement of Behavioral Objectives - taha, hamoud (Journal of Social Sciences and Humanities, 2016)
إليك الترجمة الأكاديمية للملخص الذي قدمته: Today, the desired goal in educational institutions has become preparing the learner effectively to interact and adapt to society, contribute to its development, and move away from the mere rote memorization of knowledge. This can only be achieved by equipping the learner with competencies and knowledge that allow them to face various situations and contexts. On this basis, curricula must be modernized and educational action activated by relying on the "Competency-Based Approach" as a curriculum and a framework for organizing the learning process. This approach places the learner at the core of the teaching-learning process—as an active and dynamic participant rather than a passive recipient of information, as was the case in previous pedagogies (traditional objective-based education). Under this new approach, the teacher acts merely as a facilitator, guide, and consultant for the educational process, leaving ample space for the learner to construct their own learning (self-learning). Furthermore, this approach addresses the learner across all dimensions: cognitive, skill-based, and socio-affective. It can be formulated into clear and precise procedural objectives and is closely linked to both the teacher and the learner within learning environments. Consequently, it enables the learner to: Behave appropriately and handle any situation they encounter. Act effectively. Take initiative when facing a situation—knowing what to do, which knowledge to use, and when. Mobilize a set of acquired knowledge to address the given situation. Finally, the interactions between these three variables (objectives, the teacher, and the learner) are responsible for determining the pedagogy to be followed.